Sociology of War as a New Task of Ukrainian Sociology (Global Journal of Human-Social Science, 2023)
The events taking place in modern Ukraine actualize military issues The future of Ukraine as a sovereign state depends on an objective assessment of the situation and the adequacy of its perception The role of sociology as a science that focuses on understanding social reality in our case - war is essential in this aspect Its consequences are felt not only for Ukraine but also for the international community
Keywords: war; sociology of war; micro-; meso-; macroand mega-level approaches of sociological analysis